Coup-TF1 and Coup-TF2 control subtype and laminar identity of MGE-derived neocortical interneurons - Hu, Jia Sheng (Development, 2017)
Distinct cortical interneuron (CIN) subtypes have unique circuit functions; dysfunction in specific subtypes is implicated in neuropsychiatric disorders. Somatostatin- and parvalbumin-expressing (SST(+) and PV(+)) interneurons are the two major subtypes generated by medial ganglionic eminence (MGE) progenitors. Spatial and temporal mechanisms governing their cell-fate specification and differential integration into cortical layers are largely unknown. We provide evidence that Coup-TF1 and Coup-TF2 (Nr2f1 and Nr2f2) transcription factor expression in an arc-shaped progenitor domain within the MGE promotes time-dependent survival of this neuroepithelium and the time-dependent specification of layer V SST(+) CINs. Coup-TF1 and Coup-TF2 autonomously repress PV(+) fate in MGE progenitors, in part through directly driving Sox6 expression. These results have identified, in mouse, a transcriptional pathway that controls SST-PV fate.